Profitability and Earnings Persistence Drive Earnings Management in Manufacturing Firms: Profitabilitas dan Persistensi Laba Mendorong Manajemen Laba di Perusahaan Manufaktur - Rochman, Muhamad Alif Aulia; Hermawan, Sigit (Universitas Muhammadiyah Sidoarjo, 2024)
General Background: Earnings management significantly impacts stakeholders' decisions based on reported profits. Specific Background: This study examines the effects of profitability, accounting conservatism, liquidity, and earnings persistence on earnings management in manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023. Knowledge Gap: Previous research shows inconsistent findings, particularly regarding accounting conservatism and liquidity's effects, highlighting a need for further investigation. Aims: This research aims to clarify these influences within the Indonesian manufacturing sector. Results: Using quantitative analysis of 135 firms, findings reveal that profitability and earnings persistence positively affect earnings management, while liquidity negatively impacts it. Accounting conservatism does not significantly influence earnings management. Novelty: This study incorporates earnings persistence as a critical factor, contributing to existing literature. Implications: The results suggest investors should exercise caution in their decisions due to potential financial reporting manipulation and emphasize the need for improved transparency in financial reporting practices. Highlights: Profitability and earnings persistence positively influence earnings management, indicating a tendency for managers to adjust earnings when profits are high. Liquidity shows a significant negative effect on earnings management, suggesting that firms with better liquidity are less likely to engage in earnings manipulation. Accounting conservatism does not significantly impact earnings management practices, highlighting a potential gap in the application of conservative accounting principles. Keywords: Earnings Management, Profit Persistence, Accounting Conservatism, Liquidity, Earnings Persistence